ANALISIS KUALITAS LAYANAN PASAR TRADISIONAL DI KOTA MANADO MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS (FMEA) DAN THEORY AND INNOVATIVE PROBLEM SOLVING (TRIZ) - Neyland, Johan S.C.; Rondonuwu, Irvan Raymon; Mawikere, Lidia M. (FEB Universitas Sam Ratulangi Manado, 2025)
Traditional markets are public service places where sellers and buyers meet who play a very important role in people's lives. To support the role of public services, identification and evaluation as well as improvement of various risk impacts are important activities for improving market operations for consumer satisfaction. Regarding the important functions of the market as mentioned above, this research aims to analyze the impact of market operational risks related to service quality using the Failure Mode and Effect Analysis (FMEA) and Theory and Innovative Problem Solving (TRIZ) methods. The stages of this research start from studying existing literature to become the basis for creating questionnaires, processing data to drawing conclusions. The results of the research show that there is 1 risk with the highest RPN value in the Karombasan market, namely X1 sanitation is not smooth and 2 types of risks with the highest RPN in the Bersehati market, namely X11 unclear administration and licensing and The proposed improvement using the TRIZ method is the application of Inventive Principles for risk type X1 is principle number 25 namely Self-service, make an object serve itself by performing auxiliary helpful functions, for the required change of an object (either fully or partially), and X17 the solution is based on principle number 23, namely Feedback, Introduce feedback (referring back, cross-checking) to improve a process or action. Keywords: Traditional market, Risk, FMEA, TRIZ.